2018
DOI: 10.14236/ewic/hci2018.29
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Paper- and Tool-based Participatory Design Approaches: A Case Study with PDotCapturer

Abstract: In the current Participatory Design (PD) practice, paper-based approaches are commonly applied. However, the use of software tools can potentially enhance the PD process and outcome, given their flexibility for prototype presentation, data storage, retrieval and analysis. Driven by this assumption, we developed the specific-purpose PD online tool PDotCapturer. To evaluate the effectiveness of PDotCapturer, as compared with a paper-based approach, we conducted a within-subjects study where 33 participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The applications are particularly useful in making precise calculations (e.g., the angles for the PTSOT test). One of the advantages of using software tools is that the process of data analysis is facilitated [50]. In a paper-based approach, the data must be digitized for analysis, which can be time consuming depending on the amount of data to be digitized.…”
Section: Plos Onementioning
confidence: 99%
“…The applications are particularly useful in making precise calculations (e.g., the angles for the PTSOT test). One of the advantages of using software tools is that the process of data analysis is facilitated [50]. In a paper-based approach, the data must be digitized for analysis, which can be time consuming depending on the amount of data to be digitized.…”
Section: Plos Onementioning
confidence: 99%
“…Furthermore, they also reported that older participants enjoyed the paper-based design sessions. A more recent study (Heintz et al, 2018) compared paper-based and tool-based prototypes to provide feedback on e-learning prototypes. Although this study was conducted among working adults (science teachers from different European countries), it found that the paper-based approach was able to generate more feedback.…”
Section: Introductionmentioning
confidence: 99%
“…The applications are particularly useful in making precise calculations (e.g., the angles for the PTSOT test). One of the advantages of using software tools is that the process of data analysis is facilitated (Heintz et al, 2018). In a paper-based approach, the data must be digitized for analysis, which can be time consuming depending on the amount of data to be digitized.…”
Section: Discussionmentioning
confidence: 99%